2021
DOI: 10.3389/fcomp.2021.757653
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion State Transitions in Single-Particle Trajectories of MET Receptor Tyrosine Kinase Measured in Live Cells

Abstract: Single-particle tracking enables the analysis of the dynamics of biomolecules in living cells with nanometer spatial and millisecond temporal resolution. This technique reports on the mobility of membrane proteins and is sensitive to the molecular state of a biomolecule and to interactions with other biomolecules. Trajectories describe the mobility of single particles over time and provide information such as the diffusion coefficient and diffusion state. Changes in particle dynamics within single trajectories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…, 2004 ) and it is also likely that receptors are confined before immobilization. MET receptors become immobilized due to interactions with the actin cytoskeleton and before endocytosis ( Shen et al. , 2000 ; Li et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2004 ) and it is also likely that receptors are confined before immobilization. MET receptors become immobilized due to interactions with the actin cytoskeleton and before endocytosis ( Shen et al. , 2000 ; Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…If it is not possible to learn the transition probabilities reliably from the experimental data, it is also possible to apply the proposed method using only the parameters from the diffusion mixture model. For the MET SPT data set analyzed in this study, it was shown that changes in mobility modes in single-molecule trajectories can be observed by a combined application of segmentation and mean squared displacement analysis ( Rahm et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the ability to analyze motion at the single-particle level provides a valuable body of information that is not possible to attain with purely ensemble techniques, manual handling of generated large datasets constitutes a time-consuming and prone to error process [ 24 ]. Various available software has been shown useful in aiding this task [ 25 , 26 , 27 , 28 , 29 , 30 ]. However, these solutions offer limited possibilities for data processing customization, need intermediate to advanced computing skills for installing and use, or require payment of a license (self or that of an ancillary software such as MATLAB).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tracks are often short as particles can bleach or diffuse out of the field of view or focal plane (17). In such situations, probabilistic methods are better suited to determine global parameters such as diffusion coefficients and transition rates (3, 7, 1826). Some of these methods can also predict the motion states of individual molecules at every time point (3, 7, 26, 27), which can reveal the locations of binding sites, spatial correlations, and complex, potentially non-Markovian dynamics (28).…”
Section: Introductionmentioning
confidence: 99%